2002
DOI: 10.1200/jco.2002.20.2.567
|View full text |Cite
|
Sign up to set email alerts
|

Dronabinol Versus Megestrol Acetate Versus Combination Therapy for Cancer-Associated Anorexia: A North Central Cancer Treatment Group Study

Abstract: In the doses and schedules we studied, megestrol acetate provided superior anorexia palliation among advanced cancer patients compared with dronabinol alone. Combination therapy did not appear to confer additional benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(160 citation statements)
references
References 20 publications
1
151
0
5
Order By: Relevance
“…The most common prodromal finding in patients with cancer, occurring in 31-37% [1][2][3], is weight loss. Greatest losses are seen in patients with cancer of the upper gastrointestinal tract [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common prodromal finding in patients with cancer, occurring in 31-37% [1][2][3], is weight loss. Greatest losses are seen in patients with cancer of the upper gastrointestinal tract [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The most common prodromal finding in patients with cancer, occurring in 31-37% [1][2][3], is weight loss. Greatest losses are seen in patients with cancer of the upper gastrointestinal tract [1,2]. Cytokine-mediated cachexia and side effects of toxicities of antineoplastic therapy can further exacerbate the existing involuntary weight loss [1,2,[4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…THC is effective in AIDS wasting and cancer cachexia [247]. THC (2 x 2.5 mg) was less effective than megestrol acetate (800 mg daily).…”
Section: Established Effectsmentioning
confidence: 99%
“…56,57 In multiple randomized comparison studies, megestrol acetate and synthetic tetrahydrocannabinol have been shown to be useful appetite stimulants. 58,59 In a randomized, double-blind, placebo-controlled study, patients with advanced cancer who received dronabinol had increased appetite, appreciation for food, protein consumption, and total caloric intake, as well as quality of sleep, relaxation, and QoL. 60 Similar results were seen in a 2018 study with nabilone.…”
Section: Pancreatic Cancer-related Symptom Managementmentioning
confidence: 73%